Reaction of radiometric parameters to atmospheric pollution: Part I - Variation over time (MAUSAM, 1994)
The drive for indust rial development h... ... 100 to large scale urbanisation and result,.-. d in theinjec tion of good amount of suspended particle.. and gaseous substances into the atmosphere. The m..er-abuscof the capac ity .of the atmosphere to sustain the equilibrium is bound to disturb the heal budget of the earthatmospheresystem. Radiometric parameters of the atmosphere give an early indication of the trends in the longtermclimatic changes. Whi le the global rad iant exposure is no t likely to show perceptible changes due to theincreased scauering by the pollutants, I ~ ~ diffuse radiant el(p(ls~re and the direct so.l3! irradianc~ respond qu icklyto the changes In the atmospheric conditions. Various controlling factors like humidity. soi l moist ure and cloud"have d ifferent effects on the terres trial radiant energy and the changes in thi s energy OI..'Cur slowly and ta ke longtime to affect the climate at a place. But the general trend is indicated by the increased diffuse component in thedi rect sola r rrmdiances and in the net outgoing terrestrial radia nt energy. The responses arc clearly indicative.part icularly ,II Punc......here the industrial activiti es grew at a phenomenal rate during the past fifteen years.